Successes, weaknesses, and recommendations to strengthen primary health care: a scoping review - Aklilu Endalamaw; Daniel Erku; Resham B. Khatri; Frehiwot Nigatu; Eskinder Wolka; Anteneh Zewdie; Yibeltal Assefa (BMC, 2023)
Abstract Background Primary health care (PHC) is a roadmap for achieving universal health coverage (UHC). There were several fragmented and inconclusive pieces of evidence needed to be synthesized. Hence, we synthesized evidence to fully understand the successes, weaknesses, effective strategies, and barriers of PHC. Methods We followed the PRISMA extension for scoping reviews checklist. Qualitative, quantitative, or mixed-approach studies were included. The result synthesis is in a realistic approach with identifying which strategies and challenges existed at which country, in what context and why it happens. Results A total of 10,556 articles were found. Of these, 134 articles were included for the final synthesis. Most studies (86 articles) were quantitative followed by qualitative (26 articles), and others (16 review and 6 mixed methods). Countries sought varying degrees of success and weakness. Strengths of PHC include less costly community health workers services, increased health care coverage and improved health outcomes. Declined continuity of care, less comprehensive in specialized care settings and ineffective reform were weaknesses in some countries. There were effective strategies: leadership, financial system, 'Diagonal investment', adequate health workforce, expanding PHC institutions, after-hour services, telephone appointment, contracting with non-governmental partners, a 'Scheduling Model', a strong referral system and measurement tools. On the other hand, high health care cost, client's bad perception of health care, inadequate health workers, language problem and lack of quality of circle were barriers. Conclusions There was heterogeneous progress towards PHC vision. A country with a higher UHC effective service coverage index does not reflect its effectiveness in all aspects of PHC. Continuing monitoring and evaluation of PHC system, subsidies to the poor, and training and recruiting an adequate health workforce will keep PHC progress on track. The results of this review can be used as a guide for future research in selecting exploratory and outcome parameters.